Assessement Methods of an Entity’s Economic Risks in Compiling the Accounting Policy - S. A. Kasyanova (Учёт. Анализ. Аудит, 2023)
The accounting policy of any economic entity is a strategically important tool for organizing accounting processes. Obviously, the assessment of economic activity risks affecting the choice of the most optimal accounting method allows it to identify the degree of impact of an event on the formation of accounting (financial) reporting indicators and prevent its material misstatements. Currently, in the Russian Federation, there is no methodology for assessing the risks of economic activity conducted at the legislative level for commercial organizations. The author’s working out presented in the paper fills the gap. This development is necessary in preparing the organizational, technical and methodological sections of the accounting policy of a commercial organization. It is based on the link between control procedures and risk assessment. The latter is stated in points, based on administrative responsibility for violation of the requirements for accounting and compiling of financial statements in Articles 15.11, 15.15.6 of the Code of Administrative Offenses. Also, it reflects the results of the audit, the nature of violations, and recommendations for their elimination. The study’s purpose works out a methodology for assessing the organization’s internal control system based on the development of methodological tools for identifying the consequences of the risk of economic activity at the stage of compiling the accounting policy of the commercial entity. The author used logical methods of cognition, system analysis and synthesis, modeling in practice. The significance of the results lies in deepening knowledge about the risk of economic activity, ways and methods of its assessment. The research gives a possibility to apply such tools and mechanisms in the organization’s internal control system.